China’s Policy in Central Asia (the 1990s–Early XXI Century) - E. A. Markova (Проблемы постсоветского пространства, 2022)
The article considers the evolution of Chinese policy for the countries of Central Asia, which emerged after the collapse of the USSR. The key tools of Chinese policy in this part of the post-Soviet space were trade and economic relations. Within a short time, China has managed to significantly increase the scope of trade and economic cooperation with each country in the region. A hallmark of China’s policy in Central Asia has been its evolving relations with each state in the region on a bilateral basis. The Chinese side made heavy use of such cooperation mechanisms as credit granting and infrastructure project implementing. In turn, the countries of the region were interested in expanding cooperation with China. This allowed them to support the national economies, which faced serious difficulties after the collapse of the Soviet Union. The article highlights the specificities in developing China’s relationship with each of the states, sums up the results of their interaction in the 1990s, and outlines approaches to the development of cooperation on a bilateral basis in the first decade of the 21st century. In the early part of the century, hydrocarbon resources and their delivery routes were integral to Chinese policy in the region.